Social learning, neighborhood effects, and investment in human capital: evidence from Green-Revolution India - Yamauchi, Futoshi (International Food Policy Research Institute, 2005)
This paper empirically identifies social learning and neighborhood effects in schooling investments in a new technology regime. The estimates of learning-investment rule from farm household panel data at the onset of the Green Revolution in India, show that (1) agents learn about schooling returns from income realizations of their neighbors and (2) schooling distribution of the parents’ generation in a community has externalities to schooling investments in children that are consistent with social learning. Simulations show that variations in schooling distributions within and across communities generate through social learning substantial variations in child enrollment rate and average household income. The results suggest that imperfect information hinders investment in human capital.